Increasing trend of scientists to switch between topics - An Zeng (Nature Portfolio, 2019)
How does a scientist’s tendency to explore a variety of topics affect their career? Here, the authors analyze scientific publication data to understand how often scientists switch topics, how topic switching has changed over time, and how it relates to research productivity.